2022
DOI: 10.3390/cryst12030311
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Analog of the Mineral Ivanyukite: Sorption Behavior to Lead Cations

Abstract: The production of electrolytic nickel includes the stage of leaching of captured firing nickel matte dust. The solutions formed during this process contain considerable amounts of Pb, which is difficult to extraction due to its low concentration upon the high-salt background. The sorption of lead from model solutions with various compositions by synthetic and natural titanosilicate sorbents (synthetic ivanyukite-Na-T (SIV), ivanyukite-Na-T, and AM-4) have been investigated. The maximal sorption capacity of Pb … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The Raman spectra of lintisite with L3 and kukisvumite with K3 forms are shown at Figure 14 a,b, respectively. The Raman data of the AM-4 family compounds have not previously been published and the assignments of the bands were made using analogy with structurally-related titanosilicates [ 8 , 47 , 76 , 77 , 78 ]. In general, the spectra of kukisvumite and lintisite are very close, and differ only by small shifts and in the intensity of different bands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Raman spectra of lintisite with L3 and kukisvumite with K3 forms are shown at Figure 14 a,b, respectively. The Raman data of the AM-4 family compounds have not previously been published and the assignments of the bands were made using analogy with structurally-related titanosilicates [ 8 , 47 , 76 , 77 , 78 ]. In general, the spectra of kukisvumite and lintisite are very close, and differ only by small shifts and in the intensity of different bands.…”
Section: Resultsmentioning
confidence: 99%
“…AM-4 demonstrates excellent sorption properties with respect to Pb from industrial solutions, but the molecular mechanism of this process remains unexplored [ 47 ]. It has also been observed that, in acidic environments, AM-4 loses extra-framework Na cations and H 2 O molecules, with the acid-activated form being more efficient with respect to the adsorption of N 2 and CO 2 [ 48 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the acid-resistant synthetic analogues of zeolites are the titanium silicates. Firstly the Engelhard Titanium Silicate-4, and 10 (ETS-4 and ETS-10) were synthesised [29] and lately the ETS-14 [37] and Grace titanium silicate-1 (GTS-1) [38,39] were also reported. The titanium silicates are characterised by a porous crystal framework with uniform pore size-in the case of ETS-4 about 3.7 Å, for ETS-10 about 10 Å, and for ETS-14 about 14 Å.…”
Section: Introductionmentioning
confidence: 99%
“…However, the industrial implementation requires adjustment of the activation technique to obtain materials with enhanced properties, e.g., increase the uptake of harmful components. The goal of this work is to expand the data on the sorption/exchange properties of the titanosilicate GTS-1 towards Pb(II) cations, as information on the Pb(II)exchange properties of GTS-1 is very scarce in the scientific literature [38]. The study is focused on obtaining detailed uptake equilibrium and kinetic data for Pb(II) exchange on the synthesised GTS-1 and its produced H-form.…”
Section: Introductionmentioning
confidence: 99%